2009
DOI: 10.1577/m08-062.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Fish Entrainment into Massive Water Diversions in a Tidal Freshwater Estuary: Can Fish Losses be Managed?

Abstract: Abstract.-We examined factors affecting fish entrainment at California's State Water Project and Central Valley Project, two of the largest water diversions in the world. Combined, these diversions from the upper San Francisco Estuary support a large component of the municipal and agricultural infrastructure for California. However, precipitous declines in the abundance of several estuarine fish species, notably the threatened delta smelt Hypomesus transpacificus, have generated major concern about entrainment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
146
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 114 publications
(155 citation statements)
references
References 48 publications
9
146
0
Order By: Relevance
“…It has been previously shown that estuarine species respond strongly to interannual variability in freshwater flow (Jassby et al 1995;Kimmerer 2002), though this has yet to be evaluated for Mississippi Silversides. Water diversion projects within the Delta can alter the hydrodynamics of the region and have been shown to entrain a sizeable number of Mississippi Silversides in certain years (Grimaldo et al 2009). Water temperature and turbidity may be important for Mississippi Silversides on a longer time scale based on our GAM analysis results (Question 2 above) and previous studies (Moyle 2002).…”
Section: Q3: Does Mississippi Silverside Cohort Strength Correlate Wimentioning
confidence: 99%
“…It has been previously shown that estuarine species respond strongly to interannual variability in freshwater flow (Jassby et al 1995;Kimmerer 2002), though this has yet to be evaluated for Mississippi Silversides. Water diversion projects within the Delta can alter the hydrodynamics of the region and have been shown to entrain a sizeable number of Mississippi Silversides in certain years (Grimaldo et al 2009). Water temperature and turbidity may be important for Mississippi Silversides on a longer time scale based on our GAM analysis results (Question 2 above) and previous studies (Moyle 2002).…”
Section: Q3: Does Mississippi Silverside Cohort Strength Correlate Wimentioning
confidence: 99%
“…However, resident species (i.e. those that do not emigrate from reservoirs) are also vulnerable to entrainment when they use habitats near water intake structures, with vulnerability to entrainment varying with factors such as species, life stage, time of day, season and operations (Coutant & Whitney 2000, Grimaldo et al 2009, Spinelli 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Once sediment enters the central Delta through the Georgiana Slough pathway, it is gradually advected southward though Old and Middle rivers into the south Delta; Wright and Morgan (2015) calculated a travel time of about 2 weeks from Freeport to the south Delta for a first flush sediment pulse in December 2012. This slow advection of sediment southward, which increases turbidity in the south Delta, has important implications because elevated turbidity in the region of the pumping facilities has been linked to high entrainment of Delta Smelt at the facilities (Grimaldo et al 2009), which can lead to curtailments of federal and state water deliveries.…”
Section: Anthropogenic Forcingmentioning
confidence: 99%